The Paradoxical Leishmanicidal Effects of Superoxide Dismutase (SOD)-Mimetic Tempol in Leishmania braziliensis Infection in vitro - Oliveira, Laíse B.; Celes, Fabiana S.; Paiva, Claudia N.; de Oliveira, Camila I. (Frontiers in Cellular and Infection Microbiology, 2019)
Leishmaniasis is an infectious disease caused by protozoans of the genus Leishmania. The macrophage is the resident cell in which the parasite replicates and it is important to identify new compounds that can aid in parasite elimination since the drugs used to treat leishmaniasis are toxic and present side effects. We have previously shown that treatment of L.braziliensis-infected macrophages with DETC (Diethyldithiocarbamate) induces parasite killing, in vivo. Thus, the objective of this study was to further evaluate the effect of oxidants and antioxidants in L. braziliensis-infected macrophages, following treatment with either oxidizing Hydrogen Peroxide, Menadione, DETC or antioxidant [NAC (N-Acetyl-Cyteine), Apocynin and Tempol) compounds. We determined the percentage of infected macrophages and number of amastigotes. Promastigote survival was also evaluated. Both DETC (SOD-inhibitor) and Tempol (SOD-mimetic) decreased the percentage of infected cells and parasite load. Hydrogen peroxide did not interfere with parasite burden, while superoxide-generator Menadione had a reducing effect. On the other hand, NAC (GSH-replenisher) and Apocynin (NADPH-oxidase inhibitor) increased parasite burden. Tempol surfaces as an interesting candidate for the chemotherapy of CL with an IC50 of 0.66mM ± 0.08 mM and selectivity index of 151. While it remains obscure how a SOD-mimetic may induce leishmanicidal effects, we suggest the possibility of developing Tempol-based topical applications for the treatment of cutaneous leishmaniasis caused by L. braziliensis.